Osmo-air drying of aloe vera gel cubes - Pisalkar, P. S. (Springer-Verlag, 2010)
Aloe vera (Aloe barbadensis Miller) cubes of 12.5 × 12.5 × 12.5 mm thick were osmosed for 4 h in sugar syrup of 30, 40 and 50°Brix concentration and temperatures of 30 and 50°C at constant syrup to fruit ratio of 5:1. Osmosed and unosmosed aloe vera samples were hot air dried at 50, 60, 70 and 80°C with constant air velocity of 1.5 m/s. The water loss, solid gain and convective drying behaviour were recorded during experiments. It was observed that water loss and solid gain ranged from 39.2 to 71.3 and 2.7 to 6.3%, respectively during osmo-drying. The moisture diffusivity varied from 2.9 to 8.0 × 10(−9) m²/s and 2.7 to 4.6 × 10(−9) m²/s during air drying of osmosed and unosmosed aloe vera samples, respectively. Drying air temperature and osmosis as pre-treatment affected the water loss, solid gain, diffusivity at −p ≤ 0.01